Rewriting Hippolytus: Hybridity, Posthumanism, and Social Politics in Marina Carr's Phaedra Backwards - Torrance, Isabelle (Arethusa, 2022)
This article sheds light on Irish playwright Marina Carr's 2011 Phaedra Backwards, which premiered at the McCarter Theater in Princeton, as a particularly dense and multidirectional twenty-first century retelling of the Hippolytus myth. The centrality of the Minotaur in the drama, the role of technology in his creation, the place of nature in human life, and certain surprising motifs, such as the eating of daffodils, are examined through the lens of posthumanism to show how Carr's play invites reflection on nonconformism in society and on human damage to the natural world.